Comparing the internet to others sources of information for acquiring knowledge on Takaful among Prudential BSN takaful agents - Che Mohd Salleh, Marhanum; Wok, Saodah (2011)
Malaysian Takaful industry is progressively taking innovative steps to improvise their marketing efforts via the introduction of Wakala system (agency system). Agents as one of the distribution channel for the industry play a prominent role in educating the society about the objectives and concept of Takaful. This effort may increase the awareness of the society about the Islamic insurance which remain low previously. Thus, this study is an attempt (1) to explore the sources of information that influencing the knowledge of Takaful agents; (2) to compare the contribution of the Internet and other sources of information towards understanding the objectives and concepts of Takaful by Takaful agents; and (3) to analyze the relationships between the usage of the Internet and other sources with the acquisition of knowledge on objectives and concepts of Takaful. A preliminary study was conducted with 50 Takaful agents from Prudential BSN Takaful Berhad. Data were collected through survey research design using questionnaire as the research instrument. Data gathered will be analyzed using SPSS WIN 17 for both descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (paired t-test and step-wise regression analysis).